Trypanosomatid selenophosphate synthetase structure, function and interaction with selenocysteine lyase - da Silva, Marco Túlio Alves; E Silva, Ivan Rosa; Faim, Lívia Maria; Bellini, Natália Karla; Pereira, Murilo Leão; Lima, Ana Laura; de Jesus, Teresa Cristina Leandro; Costa, Fernanda Cristina; Watanabe, Tatiana Faria [UNESP]; Pereira, Humberto D’Muniz; Valentini, Sandro Roberto [UNESP]; Zanelli, Cleslei Fernando [UNESP]; et al. (Public Library of Science (PLoS), 2020)
Eukaryotes from the Excavata superphylum have been used as models to study the evolution of cellular molecular processes. Strikingly, human parasites of the Trypanosomatidae family (T. brucei, T. cruzi and L. major) conserve the complex machinery responsible for selenocysteine biosynthesis and incorporation in selenoproteins (SELENOK/SelK, SELE-NOT/SelT and SELENOTryp/SelTryp), although these proteins do not seem to be essential for parasite viability under laboratory controlled conditions. Selenophosphate synthetase (SEPHS/SPS) plays an indispensable role in selenium metabolism, being responsible for catalyzing the formation of selenophosphate, the biological selenium donor for selenocys-teine synthesis. We solved the crystal structure of the L. major selenophosphate synthetase and confirmed that its dimeric organization is functionally important throughout the domains of life. We also demonstrated its interaction with selenocysteine lyase (SCLY) and showed that it is not present in other stable assemblies involved in the selenocysteine pathway, namely the phosphoseryl-tRNASec kinase (PSTK)-Sec-tRNASec synthase (SEPSECS) complex and the tRNASec-specific elongation factor (eEFSec) complex. Endoplasmic reticulum stress with dithiothreitol (DTT) or tunicamycin upon selenophosphate synthetase ablation in procyclic T. brucei cells led to a growth defect. On the other hand, only DTT presented a negative effect in bloodstream T. brucei expressing selenophosphate synthetase-RNAi. Furthermore, selenoprotein T (SELENOT) was dispensable for both forms of the parasite. Together, our data suggest a role for the T. brucei selenophosphate synthetase in the regulation of the parasite’s ER stress response.